Community Involvement in Preparation of EIA Documents as Implementation of Participatory Principles In Law No.32 Year 2009 About Protection and Environmental Management (Study at PT Mandiri Mining Corporindo) - Rahmat Rahmat (Susbtantive Justice International Journal of Law, 2018)
PT. Mandiri Mining Corporindo (MMC) is a mining company of Mangan in Bonehau Village, Bonehau District of Mamuju Regency, West Sulawesi Province with exploration license number 418/2009 and production operation license number 333 of 2010, where production process has started since October 2010, while the area of mining business license owned by PT.MMC is 178 ha covering 178 ha area covering production forest area 125 ha and community plantation 53 ha, but a newly managed area about 30 percent. Since the beginning of the opening of mining companies in this village has raised concerns about the negative impact of environmental damage, given the location of the mine directly bound to the plantation and rice fields of local communities. This is an interesting issue studied from the legal aspects of licensing, especially environmental permissions so that the problems in this research are; First what is the position of Environmental Impact Assesment EIA in PT.MMC environmental permit? Second, how does the community engage in the document of Environmental Impact Assesment EIA PT.MMC implementation. the results of this study indicate that the EIA position in the environmental permit is an absolute obligation and prerequisite if a company violates the environmental permit, the business license or activity may be canceled. And the PT.MMC EIA issuance procedure has been in accordance with the legislation but in its implementation is not in accordance with the planning.